(untitled) (Biological Sciences - PJSIR, 2024)
Grapevine (Vitis vinifera) is one of the significant fruit trees cultivated in Iraq. During 2018- 2019, severe leaf spot symptoms were observed commonly on grapevine in Al-Hussainiya district, Karbala province, Iraq. In order to identify the etiology of this disease, symptomatic leaf samples were collected randomly. The associated fungus was isolated, purified and identified as Alternaria alternata according to its morphological characteristics and sequence analyses of the internal transcribed spacer (ITS) region of the ribosomal DNA (rDNA). The pathogenicity assay using Koch’s postulates approved that the isolated alternata was pathogenic on grapevine leaves. The current study represents the first record of A. alternata causing leaf spots on grapevine in Karbala province, Iraq.